Interactive 3D multimedia courseware in mathematics for primary school children (3DML) / Norbaity Hariani Muhammad - Norbaity Hariani , Muhammad (2004)
Traditionally, mathematics like any other subject is being taught using books in school. The advancement technology and use of computer has made interactive learning and teaching possible. Interactive learning can be carried out anywhere as long as there's a computer. The students do not have to be at a classroom at a particular place or at a particular time. Thus, I have chosen my thesis title as "Interactive 30 Multimedia Courseware in Mathematics for Primary School Children" which I have names it as "3D Math Learning''. This courseware will create in CD-ROM based and will be suitable for primary school children especially age between 10 and 12, parents, and teachers. User will be able to choose the content by topic and can also do some exercises after learn each topic to test their understanding. One of the objective of this courseware is to help teachers and parents in teaching mathematics in English. The courseware implements the concept of multimedia, which integrates text, animations, audio and 30 graphics to make the courseware more attractive. Finally, I hope the "30 Math Learning" can serve to enable users enjoy to learn mathematics, and to achive the objective specified before the courseware is develop.